Asociación de la caries dental con el nivel de conocimiento sobre salud oral de los padres/madres de niños de 3 a 7 años de edad en una institución educativa pública del distrito de Ate - Vitarte - Muñoz Luna Victoria, Estefania (2014)
The main of this study was to determine the association between the dental caries and the parent’s oral health level knowledge of children aged 3 to 7 years of a public educational institution in the district of Ate Vitarte. This is a descriptive, observational, cross-sectional and prospective study. Two hundred and twelve children aged 3 – 7 years were examined. The clinical exam was made by one examiner calibrated by a specialist in dental caries diagnosis, in a public educational institution. It was evaluated through the epidemiological DMFT and dmft index. The parent’s oral health level knowledge was evaluated through a validated instrument by Benavente (2012). It also was taken the data of age, oral hygiene index of children and parent’s educational level. The prevalence of dental caries in children aged 3-5 was 81.51%, while in children of 6-7 years was 92.47%. There was no association between the presence of dental caries and gender. It was found association (p= 0.000) between the presence of the disease and the simplified modified in oral hygiene index in children aged 3-5 and simplified oral hygiene index in children aged 6-7. The parent’s educational level was associated with their level of knowledge (p= 0.000). However, there was no statistically significant association between the level of knowledge and presence of dental caries (p= 0.557). The study serves to describe the current problems about the level knowledge and provide educational measures to parents about oral health.